Srđan Mićić, Jovan Čavoški, ed., On the Fault Lines of European and World Politics: Yugoslavia between Alliances and Neutrality/Non-Alignment (Beograd: Institut za noviju istoriju Srbije, 2022), 506 str. (Časopis za suvremenu povijest, 2022)
Prikaz knjige